Treatment with Hypomethylating Agents before Allogeneic Stem Cell Transplant Improves Progression Free Survival for Patients with Chronic Myelomonocytic Leukemia - Kongtim, Piyanuch (Biol Blood Marrow Transplant, 2015)
The treatment of patients with chronic myelomonocytic leukemia (CMML) with transplant has not been optimized. We retrospectively reviewed the data for 83 consecutive patients with CMML (47 with CMML-1/2 and 36 with CMML progressed to acute myeloid leukemia) who received an allogeneic stem cell transplant at our institution between April 1991 and December 2013 to identify factors associated with improved survival and determine whether treatment with hypomethylating agents before transplant improves progression-free survival. The median age of the cohort was 57 years. Seventy-eight patients received induction treatment before transplant, with 37 receiving hypomethylating agents and 41 receiving cytotoxic chemotherapy. Patients treated with a hypomethylating agent had a significantly lower cumulative incidence of relapse at 3 years post-transplant (22%) than those treated with other agents (35%; p=0.03), whereas TRM at 1 year post-transplant did not significantly differ between the groups (27% and 30%, respectively; p=0.84). The lower relapse rate resulted in a significantly higher 3-year PFS rate in patients treated with a hypomethylating agent (43%) than in those treated with other agents (27%; p=0.04). Our data support the use of hypomethylating agents before allogeneic stem cell transplantation for patients with CMML to achieve morphologic remission and improve progression-free survival of these patients. Future studies are needed to confirm these findings.